Analisis Risiko Kesehatan Dan Keselamatan Kerja Pada Area Proses PT. XYZ Menggunakan Metode HIRARC - Ajeng Afriza; Sinta Dewi (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
PT. XYZ is an organization that manufactures wood products, including tables, chairs, and other domestic items. Workplace accidents are an extremely probable occurrence at PT. XYZ. Consequently, risk management is essential for reducing the occurrence of workplace accidents. The process of identifying suitable control measures is simplified through the utilization of the HIRARC method. The investigation was conducted in the grinding, sanding, lathe, drill, and corridor areas of the PT. XYZ process area. According to the findings derived from the conducted research, the hazard identification procedure yielded twenty-four indicators of peril. After calculating the 24 hazard indications, the risk level associated with the indicated hazards is determined. One is classified as extremely high risk, thirteen as high risk, eight as medium risk, and two as low risk. And company management can control hazards through the provision of safety signs, utilization of appropriate PPE, and establishment of work areas.